Dürer and his culture - Eichberger, Dagmar; Dürer, Albrecht (Cambridge University Press, 1998)
D(c)ơrer and his culture / Dagmar Eichberger and Charles Zika -- Naturalia and artefacta: D(c)ơrer's nature drawings and early collecting / Dagmar Eichberger -- Germanic patriotism in the age of D(c)ơrer / Larry Silver -- The Michelfeldt Tapestry and contemporary European literature / Wim H(c)ơsken -- Ways of seeing in the age of D(c)ơrer / Bob Scribner -- D(c)ơrer's witch, riding women and moral order / Charles Zika -- Tokens of affection: the meanings of love in sixteenth-century Germany / Lyndal Roper -- The censorship of images in Nuremberg, 1521-1527 / Christiane Andersson -- Changing German perceptions of the historical role of Albrecht D(c)ơrer / Paul Munch -- The making of D(c)ơrer in the collection of the National Gallery of Victoria / Irena Zdanowicz
Includes bibliographical references and index
Keywords: Dürer, Albrecht; Aufsatzsammlung; Konferenzschrift -- 1994 -- Melbourne; Zeithintergrund